Analisis Sistem Sertifikasi Halal Kategori Self Declare - Arifin, Hafiznur (SINOMIKA Journal: Publikasi Ilmiah Bidang Ekonomi dan Akuntansi, 2023)
With the increasing population of Muslims in the world, the need and demand for products that are guaranteed halal is very large. Every product that will be marketed to Muslims must have a halal certification issued by an institution that has the authority in halal certification. However, the offer of halal products is still very lacking. On the basis of these problems, the Provider Agency Halal Product Guarantee (BPJPH) makes a policy for a halal certification scheme with the "Self Declaring" category. This category needs to be studied further whether the scheme is the best solution to increase the number of halal certifications so that there is a balance between supply and demand for halal products. In this study, it will be discussed in detail about the mechanism of halal certification in the Self-Declare category. Then analyze the halal certification system for the declare cell category.